Narrative Theory and Music; Or, the Tale of Kundry's Tale - McClatchie, Stephen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
In recent years, narrative theory has been an influential model for many writers on music. Things in musical syntax like repetitions, expectations, and resolutions make it tempting to speak of music as narrative, as an emplotment of events, yet such a model in fact involves more narrativization than narrative. It is perhaps more fruitful to focus upon the musical side of unambiguously narrative moments.In this paper, I want to try to integrate recent approaches to musical narration by suggesting that narrative in music is a performance which functions according to the logic of the supplement. My approach will be two-fold: first, I want to justify restricting the enquiry to pre-existing narratives set to music by considering the limitations of the emplotment model; second, I shall use Kundry's Act II narrative in Wagner's Parsifal as a magnet to attract a number of narrative approaches: some will stick and some will not.